Open-flavor heavy hadron production in heavy-ion collisions - Fontoura, C. E. [UNESP]; Krein, G. [UNESP]; Valcarce, A.; Vijande, J. (American Physical Society (APS), 2025)
We study the production of open-flavor heavy hadrons in relativistic heavy-ion collisions. The hadronization in the quark-gluon plasma is described in the quark coalescence model. We evaluated yields and transverse momentum distributions. A simultaneous study of conventional and exotic hadrons is carried out. The Wigner functions are evaluated using hadron wave functions obtained from a single realistic quark model. Thus, results are presented in a single framework for the production of open-flavor heavy mesons, baryons, and exotic tetraquarks, in particular: D 0 , B 0 , Λ Q , Σ Q , Ξ Q , Ξ Q Q ′ , and T Q Q ′ ( Q , Q ′ = c or b ). The consequences of a partial restoration of chiral symmetry at the hadronization temperature are studied in detail.